2008
DOI: 10.1074/jbc.m707590200
|View full text |Cite
|
Sign up to set email alerts
|

Phospholamban Oligomerization, Quaternary Structure, and Sarco(endo)plasmic Reticulum Calcium ATPase Binding Measured by Fluorescence Resonance Energy Transfer in Living Cells

Abstract: Phospholamban (PLB) oligomerization, quaternary structure, and sarco(endo)plasmic reticulum calcium ATPase (SERCA) binding were quantified by fluorescence resonance energy transfer (FRET) in an intact cellular environment. FRET between cyan fluorescent protein-PLB and yellow fluorescent protein-PLB in AAV-293 cells showed hyperbolic dependence on protein concentration, with a maximum efficiency of 45.1 ؎ 1.3%. The observed FRET corresponds to a probe separation distance of 58.7 ؎ 0.5 Å , according to a computa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
116
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(133 citation statements)
references
References 49 publications
16
116
1
Order By: Relevance
“…Ser-16 and Thr-17 (the 2 phosphorylatable sites) are exposed to the bulk solvent, prone to interact with their respective kinases (i.e., protein kinase A and CamKII kinase, respectively). The amphipathic interactions of domain Ia with the lipid bilayer are also present in the oligomeric state of PLN, as measured by solution NMR in detergent micelles (14,50), solid-state NMR in lipid bilayers (13,52), EPR saturation transfer experiments in lipid bilayers and detergent micelles (8,12,13), and f luorescence resonance energy transfer in intact cells (46) and detergent reconstituted systems (53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ser-16 and Thr-17 (the 2 phosphorylatable sites) are exposed to the bulk solvent, prone to interact with their respective kinases (i.e., protein kinase A and CamKII kinase, respectively). The amphipathic interactions of domain Ia with the lipid bilayer are also present in the oligomeric state of PLN, as measured by solution NMR in detergent micelles (14,50), solid-state NMR in lipid bilayers (13,52), EPR saturation transfer experiments in lipid bilayers and detergent micelles (8,12,13), and f luorescence resonance energy transfer in intact cells (46) and detergent reconstituted systems (53).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, PLN does not possess a compact fold, but instead, has its 3D architecture dictated by interactions with the lipid bilayer. Several in vivo and in vitro studies have shown that PLN adopts a remarkably similar structure both in micelles and lipid bilayers (8,12,15,18,19,25,46,47), justifying the combination of restraints. In the event that restraints obtained in lipid bilayers and detergent micelles were incompatible, it is recommended that those from lipids be weighted more heavily, due to potential limitations of micelles.…”
Section: Discussionmentioning
confidence: 99%
“…FRET efficiency was calculated according to To estimate the contribution of FRET between non-interacting proteins (nonspecific FRET), we have previously used non-fluorescent PLB to compete for binding. This abolished specific FRET, leaving 4% residual nonspecific FRET (18). In another study, we used a fluorescently labeled PLB that could not participate in FRET as a competitor.…”
Section: E-fret Quantification and High Throughputmentioning
confidence: 99%
“…Cell ScoringWide-field fluorescence microscopy was performed as described previously (18). For each sample, automated acquisition of a field of 48 images was performed using a motorized stage (Prior, Rockland, MA) controlled by the MetaMorph software.…”
Section: E-fret Quantification and High Throughputmentioning
confidence: 99%
“…PLB exists as a population of homopentamers and monomers in the SR membrane, the monomer being the active form responsible for Ca 2ϩ -ATPase inhibition (3,4). Several groups have shown that there is a dynamic equilibrium between PLB pentamers, PLB monomers, and PLB-SERCA heterodimers (5)(6)(7)(8)(9). Recent studies with chemical cross-linking have suggested a simple mechanism of PLB inhibition, in which the PLB monomer competes with Ca 2ϩ for binding to SERCA2a by stabilizing a single conformational state of the enzyme ( Fig.…”
Section: ؉mentioning
confidence: 99%